Pembimbingan siswa SD sekitar lokasi pantai wisata Kastela untuk smart berplastik - Eko Purnomo; Darmawati Darmawati; Wawan S. Nadra (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The issue of increasing waste quantities, which are directly proportional to the human population in a region, has become a significant concern within the context of environmental sustainability. Urban areas, being centers of education and economy, often face challenges in managing the daily volume of waste generated. The accumulation of such waste has adverse impacts on the environmental quality, including water, soil, and air. One proposed solution to address this problem is to enhance the understanding of waste management from an early age to adulthood. This engagement focuses on providing elementary school students with an understanding of smart waste management through interactive and play-based approaches. The methods employed in this engagement include lectures, demonstrations, and explorations. The engagement involves 30 students from elementary schools, selected using a purposive sampling technique. The findings demonstrate that the interactive and play-based approach effectively enhances students' understanding and environmental awareness. Furthermore, the students are able to implement initial steps in waste management, such as segregating organic and inorganic waste. The successful implementation of this engagement has yielded positive outcomes in increasing students' awareness and skills in waste management. The interactive and play-based approach has proven to be effective in instilling a meaningful understanding of responsible and sustainable waste management. It is hoped that activities of this nature can be continually enhanced and expanded in an effort to create a community that is more environmentally conscious.